2010
DOI: 10.1016/j.tig.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Robustness and Evolvability

Abstract: Why isn’t random variation always deleterious? Are there factors that sometimes make adaptation easier? Biological systems are extraordinarily robust to perturbation by mutations, recombination, and the environment. It has been proposed that this robustness might make them more evolvable. Robustness to mutation allows genetic variation to accumulate in a cryptic state. Switching mechanisms known as evolutionary capacitors mean that the amount of heritable phenotypic variation available can be correlated to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
228
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(232 citation statements)
references
References 90 publications
(145 reference statements)
4
228
0
Order By: Relevance
“…We next consider evolvability, which is most readily detected when the organism is under stress (29) or when acquiring new capacities such as during external training in our experiment. We found that the community organization of brain connectivity reconfigured adaptively over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next consider evolvability, which is most readily detected when the organism is under stress (29) or when acquiring new capacities such as during external training in our experiment. We found that the community organization of brain connectivity reconfigured adaptively over time.…”
Section: Resultsmentioning
confidence: 99%
“…The accompanying system decomposability provides necessary structure for complex reconfigurations. Modularity can be a property of morphology, as has been widely described in the context of evolution and development (11,12,29), as well as of the interconnection patterns of social, biological, and technological systems (30,31). More pertinent to this paper, recent evidence suggests that modular organization over several spatial scales, or hierarchical modularity, also characterizes the large-scale anatomical connectivity of the human brain (27,28), as well as the spontaneous fluctuations (35,36) thought to stem from anatomical patterns (37).…”
Section: Discussionmentioning
confidence: 99%
“…Other recent reviews have focused on phenotypic variability and its relationship to recombination [17], enzyme promiscuity [18], commonalities among different system classes [19] and phenotypic constraints [20]. In contrast, this review's focus is the role of robustness in phenotypic variability.…”
Section: Introductionmentioning
confidence: 99%
“…Such higher order effects have always been questioned in biology, since they might be expected, in real populations, to be swamped by direct selective effects (Pigliucci, 2008). However, discussion has intensified recently over the concepts of 'robustness' and 'evolvability' (Masel and Trotter, 2010). These are higher order effects of somewhat unclear definition; the latter potentially relates directly to the control of mutation rate considered here.…”
Section: Discussionmentioning
confidence: 95%